Confined Concrete in Fiber-Reinforced Polymer Partially Wrapped Square Columns: Axial Compressive Behavior and Strain Distributions by a Particle Image Velocimetry Sensing Technique - Yong-Chang Guo; Shu-Hua Xiao; Jun-Wei Luo; Yu-Yi Ye; Jun-Jie Zeng (Sensors, 2018)
Strengthening existing reinforced concrete (RC) columns using a partial wrapping strengthening technique (PWST) by fiber-reinforced polymer (FRP) strips has been widely implemented. However, compared with the confinement mechanism of confined concrete in columns strengthened with the FRP full wrapping strengthening technique (FWST), the confinement mechanism of confined concrete in FRP partially wrapped columns is less understood. This paper presents the results of an experimental investigation into the behavior of confined concrete in FRP partially wrapped square columns under axial compression. The effects of FRP strip width and thickness on stress–strain behavior were thoroughly investigated. The novel particle image velocimetry (PIV) non-contact strain sensing technique was adopted to measure the strain in the specimens. Results show that the axial strains as well as the hoop strains are generally larger at the mid-plane of adjacent FRP strips than those at the mid-plane of each FRP strip, and considerable variation in hoop strains along the height of the specimens was observed. Comparisons between the experimental results and predictions by existing design-oriented stress–strain models were carried out to examine the accuracy of the models. A new design-oriented stress–strain model is proposed for confined concrete in FRP partially wrapped square columns and the comparisons between laboratory results and predictions from the proposed model show that the proposed model is superior to the existing models.